An empirical analysis of trading volume and return volatility in using GARCH model: the Malaysia case / Tan Yan Ling and Toy Bee Hoong - Tan, Yan Ling; Toy, Bee Hoong (2011)
The relationship between trading volume and return volatility has long been debated either on the contemporaneous correlation as explained by the mixture distribution hypothesis (MDH) or causal (lead-lag) relation as suggested by the sequential information arrival hypothesis (SIAH).The former is proposed by Clark (1973), and the latter by Copeland (1976) and Jennings, Starks, and Fellingham (1981).The purpose of this study is empirically to test the relationship between trading volume and return volatility from 3 January 2000 to 31 July 2008 in Malaysia. In this study, GARCH model is chosen because it gives better estimates in modeling return volatility. The contemporaneous correlation is tested by employing simultaneous approach (GARCH-cum trading volume). Our results strongly support the MDH hypothesis since both variables are found to follow a contemporaneous correlation pattern in Malaysia stocks. Moreover including trading volume in the conditional variance (return volatility) equation leads in a reduction of volatility persistence. We also suggest that trading volume is a good proxy of information arrival in the GARCH model. Therefore, the changes in trading volume can be used when formulating new strategy, instead of taking into account of changes in price.